Blended learning or face-to-face? Does Tutor anxiety prevent the adoption of Learning Management Systems for distance education in Ghana?. (3rd May 2020) - Bervell, Brandford; Umar, Irfan Naufal
ABSTRACT: Learning Management System (LMS)-enabled blended learning has been adopted by higher educational institutions for promoting accessible and effective pedagogy and andragogical practices. The introduction of this mode of learning has altered the traditional face-to-face interaction. However, the lack of actual usage and online presence by instructors in an LMS-enabled blended learning environment seems to be a major setback for its success. Consequently, LMS-related anxiety has been cited as one of the behavioural challenges hindering its usage in Africa. Hence, this paper is focused on unravelling the antecedents of tutors' anxiety towards actual LMS usage based on a Technology Related Stimulus-Response Theoretical Framework (TR-SR-TF). In view of this, the study employed a survey design, adopting a questionnaire as data collection instrument from 267 distance education tutors across study centres within Ghana. The results from Partial Least Squares Structural Equation Modelling (PLS-SEM) technique revealed three underlying factors determining LMS anxiety, namely; colleague influence, outcome expectation and use support. However, the result of the Importance Performance Map Analysis (IPMA) showed that colleague influence was the most important indicator while outcome expectation was the highest performance indicator of tutors' LMS related anxiety. The study recommended that such factors like colleague influence, outcome expectation and use support should be consciously addressed in order to reduce (if not totally eliminate) anxiety towards LMS use for blended learning.